Angular distributions and rovibrational excitation of N2 molecules recombined on N-covered Ag(1 1 1) by the Eley?Rideal mechanism - Juaristi, J.I. (2015)
Former calculations showed that atomic N incident at energies of a few eV on N-covered Ag(1 1 1) forms N2 molecules by the Eley?Rideal (ER) mechanism, i.e. by direct pick-up of adsorbates. Here, we calculate the azimuthal angle distributions and the rovibrational energies of those ER products. We observe a non-trivial angle dependence that may result in very low in-plane ER yield for some given incident azimuthal angles. We find that most of the energy released upon N N bond formation, about 7 eV, is stored in the rovibrational degrees of freedom independently of the incidence energy considered.